POLITICAL COMMUNICATION OF THE INCUMBENT REGENT OF BANGGAI TO INCREASE ELECTABILITY IN THE 2024 BANGGAI REGIONAL ELECTION CONTESTATION - Setiadi, Muh. Darmawan; Sadono, Teguh Priyo; Tachopisalwong, Attanan (ASPIKOM Jabodetabek Region, 2024)
This study examines the political communication implemented by the incumbent Regent of Banggai in an effort to increase electability in the 2024 Banggai Regional Election. Amidst increasing voter rationality and the complexity of local political dynamics, political communication has become a crucial instrument for building image, expanding support, and strengthening leadership legitimacy. This study uses a qualitative approach with a case study design and applies Harold D. Lasswell's communication model of Who says what in which channel to whom with what effect? to analyze the communication carried out. The main informants in this study consisted of eight figures, including the incumbent, his winning team, and coalition party leaders. The results show that the incumbent acts as the main communicator with a political narrative that emphasizes development success, increased regional budget (APBD), religious character, and social closeness. The communication channels used include formal channels (mass media, billboards, and government forums), informal channels (field visits, face-to-face), and digital channels (Instagram, TikTok, and Facebook), which are tailored to voter segmentation, such as religious voters, millennials, rational voters, and swing voters. The communication effects showed a significant increase in electability, public engagement, and the formation of a positive image of the incumbent as a religious, responsive, and visionary leader. By integrating a media convergence approach, values-based messaging, and structured audience segmentation, the incumbent's political communication strategy proved effective in maintaining and expanding public support. This research contributes to the development of political communication studies, particularly in the local context and regional head elections.